2012
DOI: 10.5588/ijtld.11.0210
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of HIV-infected patients treated for recurrent tuberculosis with the standard retreatment regimen

Abstract: SETTING AIDS and tuberculosis center in Port-au-Prince, Haiti. OBJECTIVE To measure the effectiveness of tuberculosis retreatment with the standard regimen (2HRZES/1HRZE/5HRE) in HIV-infected adults. DESIGN Cohort study. RESULTS Of 1,318 HIV-infected patients with access to antiretroviral therapy following World Health Organization guidelines, 56 were diagnosed with recurrent pulmonary tuberculosis and retreated with the standard regimen. Ten patients (18%) died during retreatment, 3 patients (5%) defaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Age, sex, residence, education, timing of treatment initiation, and HIV status at TB diagnosis were included in adjusted models based on their previous association with TB treatment outcomes. 11,22 Variables were treated categorically. Weight was excluded due to a high proportion of missing data and our hypothesis that weight may not be missing at random.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, sex, residence, education, timing of treatment initiation, and HIV status at TB diagnosis were included in adjusted models based on their previous association with TB treatment outcomes. 11,22 Variables were treated categorically. Weight was excluded due to a high proportion of missing data and our hypothesis that weight may not be missing at random.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that adolescents who start treatment have outcomes similar to those of adults on anti-tuberculosis treatment in Haiti. [22][23][24] This is encouraging, considering that adolescents have worse treatment outcomes for similarly stigmatised diseases such as HIV. 25,26 However, our study also includes data on the number of adolescents lost between TB testing and initiating anti-tuberculosis treatment, part of the care cascade that is rarely captured, 24,27 and shows that the greatest loss (16%) of patients occurred between diagnosis and treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, The World Health Organization (WHO) recommended that people presenting with TB in settings with a low prevalence of multidrug-resistant TB (MDR-TB) who have previously been treated were prescribed a standardised regimen consisting of Rifampicin(R), Isoniazid(H), Pyrazinamide(Z), Ethambutol(E) and Streptomycin(S) for 2 months, followed by RHZE for 1 month and then RHE for 5 months [3]. This ‘Category II’ regimen has no clinical trial evidence base, and treatment outcomes in this group of patients are persistently reported to be poor [4–7]. The most recent WHO TB treatment guidelines therefore recommend discontinuation of the Category II regimen where possible in favour of regimens which are guided by the results of drug susceptibility testing (DST) [8].…”
Section: Introductionmentioning
confidence: 99%
“… 36 In a study by McGreevy et al, follow-up data demonstrated that only 46% of HIV-positive patients remained alive, in ART care and TB-free after a median of 36 months of follow-up. 46 …”
Section: Resultsmentioning
confidence: 99%